Synthesis and Density Functional Theory Studies of Octakis(propyl) Porphyrazine and Its Fe(II) Complex - K. Mongale, Millicent; A Isabirye, David; M. Kabanda, Mwadham; E. Ebenso, Eno (Asian Journal of Chemistry, 2012)
The synthesis and characterization of metallated porphyrazine compounds is gaining increasing attention because of the numerous functionalities for this class of compounds. In this study synthesis and quantum chemical calculations (utilizing the B3LYP/6-31G(d,p) method) on 2,3,7,8,12,13,17,18-octakis(propyl)porphyrazine ligand and its iron metallated complex have been investigated to determine the metallation effects on the electronic and geometric properties of the ligand. The time-dependent density functional theory (TDDFT) approach was utilized for the analysis of the UV-visible spectra. The variation in geometric parameters, HOMO-LUMO gap, dipole moment and Mulliken atomic charges suggest that metallation induces significant geometric changes that is dependent on the spin state of iron. A comparison of porphyrazine ligand and 2,3,7,8,12,13,17,18-octakis(propyl)porphyrazine ligand suggests that alkylation has minimal influence on the geometry of the porphyrazine moiety.